Solving Richards’ nonlinear PDE modeling dynamic from water in unsaturated zone by a new numerical method called SBA - Yelingue, Ben-Sthal Sakoma; Sawadogo, Wenddabo Olivier; Some, Blaise (International Journal of Applied Mathematical Research, 2017)
In this paper the partial derivative equation strongly nonlinear of Richards which models the dynamics of water in the Un-saturated Zone (UZ) was linearized and solved by a new numerical method called SBA. The analytical solution has been simulated in order to be applied later to the following in unsaturated zone with the aquifers of Bangui and its boundaries.